MENUMBUH KEMBANGKAN NILAI KARAKTER KEPEMIMPINAN MELALUI BUDAYA ORGANISASI POSITIF DI SMK SASMITA JAYA 1 - Radjib, Mohammad; Dadan, Dadan; Zikrine, Zikrine; Zulia, Ilma; Suprihatin, Suprihatin (Yayasan Education and Social Center, 2024)
Implementing organizational basics, such as a clear vision and mission, inspirational leadership, strong organizational culture, and a transparent evaluation system, can significantly increase the effectiveness of character education. Apart from that, the integration of character education into the curriculum and extracurricular activities is also a determining factor in forming students' character. This research concludes that character education based on organizational fundamentals not only improves the moral quality of individuals, but also creates an educational environment that is conducive to the holistic development of students. Community service activities that focus on implementing character education based on organizational fundamentals at the Sasmita Jaya 1 Pamulang Vocational School. This activity aims to strengthen character values ??among students through a structured approach and based on organizational principles. The method used in this activity is a seminar. Implementation of the activity begins with a needs analysis and determining the vision and mission of character education in accordance with the school's culture and values. Furthermore, intensive training is carried out to integrate character values ??in the learning process and extracurricular activities. The character programs developed include various activities such as group discussions, community service projects, and competitions that encourage positive behavior. The results of the activities showed a significant increase in awareness and application of character values ??by students, as well as improvements in the school climate which was more conducive to learning. Continuous evaluation through surveys and observations shows that an organization-based character education approach has a positive impact on students' moral and ethical development